RIGHT TO RECALL ELECTED REPRESENTATIVE: MAKES SENSE IN INDIAN PARLIAMENTARY DEMOCRACY - Prabhat Deep,; Kumar, Gyanendra (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study examines the relevance of ‘right to recall the elected representative of the Parliament and assembly.’ Recall of elected represenatives is widely accepted in the western democracies and daily new development can be sensed in this area. It is considered as one of the reforms in electoral processes to strengthen democracy. Therefore, it contains a lot of information starting from definition, history, how western democracies practice this tool of recall and how flawed democratic countries are making effort to bring this instrument in their governance system with the benefits and shortcomings of this method. The work in view of the problem of evolving distrust in democracy, its institutions and manner of negating expectations of people attains its significance by presenting some viable options. It does take note of the desperate people throughout the world aspiring for reforms as their disappointment can be witnessed from demonstrations on the streets, famous squares, in front of institutions fearlessly. It considers how the misconduct of incompetent elected representatives especially at centre and state level is influencing governance and examines if right to recall can serve as an antidote in India. It focuses on two aspects that right to recall may address issue of non-accountability and strengthen the ‘we the people’ which is the real source of sovereign power of democratic set up. In last it contains conclusion and gives, suggestions for incorporating this tool with modern technology, in episodic and on trial basis in some state assembly for Constitutional governance in India